A Study of Banjarmasin City's Toponyms as a Learning Resource for Local History Based on Wetland Wisdom - Mansyur Mansyur; Rusdi Effendi; Daud Yahya; Mohamad Zarnal Arifin Anis (Yupa: Historical Studies Journal, 2025)
The city of Banjarmasin has a long history, reflected in the place names (toponyms) scattered across its territory. Toponyms not only indicate locations but also encapsulate historical, cultural, and local wisdom values of the wetland communities. Unfortunately, the use of toponyms as a source for learning local history remains limited, particularly within the educational context. This research aims to identify and describe the toponyms in Banjarmasin, along with their origins and meanings. It also analyzes the connection between toponyms and local history as well as the wisdom of the wetland communities. Furthermore, it seeks to develop a model or teaching material for local history based on toponyms as a contextual learning resource for junior and senior high schools. The research employs historical methods, including heuristics (source collection), criticism (external and internal), interpretation (analysis), and historiography (writing). The study’s findings suggest that Banjarmasin’s toponyms can be integrated into local history education. Through toponyms, students can learn about the relationship between humans and their environment, the dynamics of settlement, the city’s development over time, and support a contextual learning approach.